Lyme carditis with complete heart block: management with an external pacemaker - Chaudhry, Muhammad Ali (Clin Case Rep, 2017)
Timely diagnosis and prompt initiation of treatment is essential in Lyme carditis to achieve favorable prognosis. Externalized permanent pacemaker with an active fixation lead as supportive pacing modality is a feasible option till complete resolution of conduction block with continued antibiotic therapy.